Manāhij Naqd Al-Kitāb Al-Muqaddas fī Ad-Dirāsāt Al-Qur`āniyyah - Aqdi Rofiq Asnawi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
The usage of biblical criticism as methods to approach the Qur’an have raised doubts about its authenticity. It begins with the assumption that several faults in Bible also found in the Koran. The qur’anic text is also worthy of criticism since it assumed as only written document, which is not also have being memorized for centuries in mind. This paper tries to analyze some of biblical criticisms and their employment in the qur’anic studies in order to find out more than the assumptions and the results of studies, with focusing on textual criticism that applied by Arthur Jeffery in his various works. In order to achieve its goals, this library research employ descriptive-analysis methods to outline critically the usage of those biblical criticisms. The result of this study indicates that various qur’anic studies using Biblical criticism have a number of methodological weaknesses, such as the use of invalid reference sources, distortion of facts by changing the reference text, and faults of understanding the sources.